2014
DOI: 10.1121/1.4838995
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of age and hearing loss on interaural phase difference discrimination

Abstract: The discrimination of interaural phase differences (IPDs) requires accurate binaural temporal processing and has been used as a measure of sensitivity to temporal envelope and temporal fine structure (TFS). Previous studies found that TFS-IPD discrimination declined with age and with sensorineural hearing loss (SNHL), but age and SNHL have often been confounded. The aim of this study was to determine the independent contributions of age and SNHL to TFS and envelope IPD discrimination by using a sample of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
71
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 58 publications
12
71
3
Order By: Relevance
“…3.3, suggested that hearing loss adversely affected the discrimination of ITD carried in ENV p , King et al (2014) found that thresholds for detecting IPDs in ENV p were not significantly correlated with absolute thresholds. Also, Léger et al (2015) reported that thresholds for detecting IPDs in ENV p were similar for subjects with normal and impaired hearing (both groups had a wide range of ages).…”
Section: Binaural Processing Of Envmentioning
confidence: 99%
See 2 more Smart Citations
“…3.3, suggested that hearing loss adversely affected the discrimination of ITD carried in ENV p , King et al (2014) found that thresholds for detecting IPDs in ENV p were not significantly correlated with absolute thresholds. Also, Léger et al (2015) reported that thresholds for detecting IPDs in ENV p were similar for subjects with normal and impaired hearing (both groups had a wide range of ages).…”
Section: Binaural Processing Of Envmentioning
confidence: 99%
“…The study of King et al (2014), described above, is relevant here. Recall that they tested 46 subjects with a wide range of ages (18-83 years) and degrees of hearing loss.…”
Section: Binaural Processing Of Tfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptual difficulties observed with age in processing competing sound stimuli may depend on a variety of factors, including the fidelity of the auditory information entering the system at the level of the auditory nerve (AN), processing of this information by brainstem, midbrain, and forebrain nuclei in the central auditory pathway, integration of binaural spatial and temporal information, as well as the effects of non-auditory cognitive mechanisms such as attention (Grimault et al 2001;Alain and McDonald 2007;Bidet-Caulet et al 2007;Ruggles et al 2012;Johnsrude et al 2013;Sergeyenko et al 2013;Bharadwaj et al 2014;King et al 2014). Understanding the changes that occur in processing sound in the auditory periphery will help separate out the deficits inherited from earlier stages from those generated in the later stages of the auditory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…All tones had a frequency of 500 Hz, amplitude modulated (AM) at 20 Hz to a depth of 100%. In one condition IPDs were created in the TFS of the AM tone, in a second condition IPDs were created in the envelope (King et al, 2014;Lacher-Fougère and Demany, 2005). At the beginning of each block ΔΦ was set to 180°.…”
Section: Peripheral Processing Of Tfs and Envelope Cuesmentioning
confidence: 99%